2015
DOI: 10.1142/s0218348x1540006x
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Fractal Modeling of Permeability for Fibrous Porous Media

Abstract: Permeability is an important hydraulic parameter for characterizing heat and mass transfer properties of fibrous porous media. However, it is difficult to be quantitatively predicted due to the complex and irregular pore structure of fibrous porous media. Fractal geometry has been verified to be an effective method for determining the permeability of fibrous porous media. In this study, recent works on the permeability of fibrous porous media by means of fractal geometry are reviewed, the advances for each pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(38 citation statements)
references
References 70 publications
0
38
0
Order By: Relevance
“…Existing research found that fractal characteristics have a significant influence on gas adsorption/flow capacities, especially on the permeable pathways for methane transport during shale gas extraction, indicating that fractal properties probably influence the shale gas production and thus can be used as a parameter to evaluate the quality of a shale reservoir. [17][18][19] Therefore, improving the fractal characterization of pore structures in shale is of great importance for shale gas exploration and exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research found that fractal characteristics have a significant influence on gas adsorption/flow capacities, especially on the permeable pathways for methane transport during shale gas extraction, indicating that fractal properties probably influence the shale gas production and thus can be used as a parameter to evaluate the quality of a shale reservoir. [17][18][19] Therefore, improving the fractal characterization of pore structures in shale is of great importance for shale gas exploration and exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of the proposed model was verified by comparing the predictions to available numerical simulation results. Natural fractured rock masses are constituted by rock matrix and discontinuities (Cai et al 2014;Ma 2015), and the former one is a kind of porous media (Cai et al 2015;CuetoFelgueroso and Juanes 2016). A number of dual-porosity models have been established to quantify the permeability of porous media (Bibby 1981;Elsworth and Bai 1992;Vogel et al 2000;Li Y and Yu 2013).…”
Section: Permeability and Fracture-length Distributionmentioning
confidence: 99%
“…By introducing fractal theory, Cai et al (2010a) studied the SI law of single tortuous capillary. Furthermore, they developed this theory and made many applications in porous media based on fractal geometry (Cai et al, 2010b(Cai et al, , 2012(Cai et al, , 2014(Cai et al, , 2015. Sang (2012) studied the SI characteristics of a symmetric tree-like structure.…”
Section: Introductionmentioning
confidence: 99%